Prognostic analysis of inflammatory response-related genes and biomarkers in patients with urothelial carcinoma of ureter - Chen, Huaian; Liu, Shuo; Li, Xiujun; Wang, Zhe; Zhang, Chao (Frontiers in Genetics, 2023)
Urothelial Carcinoma of Ureter is a common urinary system tumor, accounting for 40%-60% of all Urothelial Carcinoma of Ureters. About 100,000 new cases of ureteral cancer are diagnosed in the United States each year, and 20% to 25% of them will eventually develop Urothelial Carcinoma of Ureter. Inflammatory reaction is a common clinical pathological process, which can occur in tissues and organs of various parts of the body, such as folliculitis, tonsillitis, pneumonia, hepatitis, nephritis, etc. This article attempted to analyze the prognosis of patients with Urothelial Carcinoma of Ureter through the genes and biomarkers of inflammatory response. In this paper, the co-expression network analysis and image fusion evaluation of genes were proposed, and based on this research, the prognosis results of patients with urothelial carcinoma of the ureter were analyzed. The experimental results in this paper showed that elevated levels of PLR and NLR, decreased levels of HGB and HCT, high levels of PLR and high NLR, low levels of HGB and low HCT were all risk factors affecting bladder urothelial carcinoma, and their odd ratio (OR) values were 1.023, 1.611, 0.961, 0.859, 1.015, 1.072, 0.979 and 0.951, respectively. However, high NLR level and high NLR level were independent risk factors for bladder urothelial carcinoma, and their OR values were 1.497 and 1.071. Through the diagnosis of biomarkers, the area under the curve, sensitivity, specificity, and Youden index of hsa-mir-17, hsa-mir-93, hsa-mir-429, and hsa-mir-20a all exceeded 0.9, indicating that this is a potential diagnostic indicator. All in all, during the treatment of ureteral cancer, in order to reduce tumor recurrence, it should be combined with systemic therapy for ureteral cancer. In addition, the prognosis of chemotherapy patients was also analyzed, indicating that during chemotherapy, immunotherapy may increase the risk of tumor cell reperfusion during chemotherapy.